Development of Canva-based Printed Comic Media on Fourth Grade Photosynthesis Material of SD Negeri Tepungsari - Pratiwi, Tiwi Meilita; Sari, Sasmita (Papanda Publisher, 2025)
This study aims to improve and test the validity and praticality of Canva-based printed comic Learning media on photosynthesis materials for fourth grade students. The development Model applied is ADDIE, which includes the stages of analysis, design, development, implementation, and evaluation. According to the validation results of media, language, and material experts, comic media is considered very valid, with an average validity of 84,73%. The practical test showed that themedia isvery pratical, with a response rate of 82,85% from students and 81,64% from teachers. Comic Media is considered to be able to display the process of photosynthesis visually in an interesting and easy to understand way, which is in line with the characteristics of the cognitive development of elementary school students. This research shows that the application of Canva-based print comic media in the science learning prosess is feasible.